Clinical phenomenology of suicidal behavior in dementia of various types - Mudrenko, Irina (ScienceRise: Medical Science, 2018)
Aim. The study of clinical phenomenology of suicidal behavior in patients with different types of dementia aimed at defining the predictors and preventing the development of suicidal behavior within the above-mentioned category of patients. Materials and methods. Based on the clinical and anamnestic examination of 213 patients, we studied clinical phenomenology of suicidal behavior in dementia of various types. 75 patients with Alzheimer’s disease, 73 patients with vascular dementia and 60 patients with mixed dementia were examined. The main group consisted of patients with suicidal risk, the control group included patients without manifestations of suicidal behavior. Results. Thus, in case of Alzheimer’s disease anti-vital utterances (41 %) and thoughts (50 %) prevailed. Vascular dementia was characterized by outward behavioral manifestations of suicidal behavior (suicidal intentions (25.6 %), suicidal attempts (33.33 %) and anti-vital utterances (35.9 %). Patients with mixed dementia in 50 % of cases had suicidal intentions and in 66.7 % suicidal thoughts. The most typical suicidal attempt for the patients with vascular dementia was suicide by hanging (p≤0.05), and for the patients with mixed dementia a fall under moving transport prevailed (p≤0.05). Conclusions. There has been determined the relationship between mild dementia and the ideational component of suicidal behavior (thoughts, mood) as well as between mild dementia and outward behavioral manifestations (attempts, intentions and utterances). The presence of an additional depressive syndrome in dementia correlates with suicidal thoughts and mood; and a hallucinatory syndrome along with mixed symptomatology is connected with suicidal attempts and intentions